2020
DOI: 10.1111/dth.13585
|View full text |Cite
|
Sign up to set email alerts
|

Folliculotropic mycosis fungoides: Clinical characteristics, treatments, and long‐term outcomes of 53 patients in a tertiary hospital

Abstract: Folliculotropic mycosis fungoides (FMF) is characterized by a broad clinical spectrum and worse prognosis compared to classical MF. This study aimed to evaluate the clinical characteristics, treatment modalities and long‐term outcome and risk factors for progression and survival of FMF patients. We conducted a single‐center retrospective study and reviewed 53 patients diagnosed with FMF between 1990 to 2019 in a referral center at Ankara University, Turkey. Regarding to stage at diagnosis, 24 patients (45.3%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Stage IIA showed higher LDH levels (43.5%) compared to stage IA and IB (6.7% and 8.9%, respectively) 4 . In folliculotropic MF patients, elevated LDH levels were associated with 5.53 times increased mortality compared to FMF patients with normal LDH levels 25 …”
Section: Lactate Dehydrogenase Levels and Prognosismentioning
confidence: 86%
See 4 more Smart Citations
“…Stage IIA showed higher LDH levels (43.5%) compared to stage IA and IB (6.7% and 8.9%, respectively) 4 . In folliculotropic MF patients, elevated LDH levels were associated with 5.53 times increased mortality compared to FMF patients with normal LDH levels 25 …”
Section: Lactate Dehydrogenase Levels and Prognosismentioning
confidence: 86%
“…FMF can present like classic MF with patches, plaques, tumors, and erythroderma. However, FMF can also manifest with acneiform lesions, grouped follicular lesions, and plaque lesions involving the head and neck and extremities 25,43 . In one study, head and neck involvement was observed in 75% of FMF patients with advanced stage and was associated with poor prognosis 25 .…”
Section: Folliculotropic Mycosis Fungoides and Prognosismentioning
confidence: 99%
See 3 more Smart Citations